A targeted liquid cultivation method for previously uncultured non-colony forming microbes - Seo, Eun-Young; Jung, Dawoon; Epstein, Slava S.; Zhang, Weiyan; Owen, Jeffrey S.; Baba, Hiroaki; Yamamoto, Akina; Harada, Mifuyu; Nakashimada, Yutaka; Kato, Setsu; Aoi, Yoshiteru; He, Shan (Frontiers in Microbiology, 2023)
A great number of microbes are not able to form colonies using agar plating methods, and this is one of the reasons that cultivation based on solid media leaves the majority of microbial diversity in the environment inaccessible. We developed a new Non-Colony-Forming Liquid Cultivation method (NCFLC) that can selectively isolate non-colony-forming microbes that exclusively grow in liquid culture. The NCFLC method consists of physically separating cells using dilution-to-extinction (DTE) cultivation, then selecting those that could not grow on solid medium. NCFLC was applied to marine samples from a costal intertidal zone and soil samples, and the results were compared with those from the standard direct plating method (SDP). NCFLC yielded fastidious bacteria from marine samples such as Acidobacteriota, Epsilonproteobacteria, Oligoflexia and Verrucomicrobiota. Furthermore, 62% of the isolated strains were potential new species, whereas only 10% were novel species from SDP. From soil samples, isolates belonging to Acidobacteriota and Armatimonadota were exclusively isolated by NCFLC, which are known as rare species among identified isolates. Colony formation capabilities of isolates cultivated by NCFLC were tested using solid agar plates, among which approximately one third were non-colony-forming, half formed micro-colonies, and only a minority could form ordinary size colonies. This indicates that the majority of strains cultivated by NCFLC are previously uncultured microbial species unavailable using the SDP method. We conclude that the NCFCL method can serve as a new approach to access the hidden microbial dark matter.